Shigellosis Cases With Bacterial Sexually Transmitted Infections: Population-Based Data From 6 US Jurisdictions, 2007 to 2016. Issue 8 (4th August 2022) - Ridpath, Alison D.; Vanden Esschert, Kayla L.; Bragg, Sarah; Campbell, Stephanie; Convery, Christine; Cope, Anna; Devinney, Katelynn; Diesel, Jill C.; Kikuchi, Nicole; Lee, Nicole; Lewis, Felicia M.T.; Matthias, James; et al.
Abstract : From 2007 to 2016, 20% of male shigellosis case-patients from 6 US jurisdictions had at least 1 bacterial sexually transmitted infection (chlamydia, gonorrhea, or syphilis) reported 12 months before or after the shigellosis case report; 4% of female shigellosis cases had a sexually transmitted infection. Abstract : Background: Shigella species, which cause acute diarrheal disease, are transmitted via fecal-oral and sexual contact. To better understand the overlapping populations affected by Shigella infections and sexually transmitted infections (STIs) in the United States, we examined the occurrence of reported STIs within 24 months among shigellosis case-patients. Methods: Culture-confirmed Shigella cases diagnosed from 2007 to 2016 among residents of 6 US jurisdictions were matched to reports of STIs (chlamydia, gonorrhea, and all stages of syphilis) diagnosed 12 months before or after the shigellosis case. We examined epidemiologic characteristics and reported temporal trends of Shigella cases by sex and species. Results: From 2007 to 2016, 10, 430 shigellosis cases were reported. The annual number of reported shigellosis cases across jurisdictions increased 70%, from 821 cases in 2007 to 1398 cases in 2016; males saw a larger increase compared with females. Twenty percent of male shigellosis case-patients had an STI reported in the reference period versus 4% of female case-patients. The percentage of male shigellosis case-patients with an STI increased from 11% (2007) to 28% (2016); the overall percentage among females remained low. Conclusions: We highlight the substantial proportion of males with shigellosis who were diagnosed with STIs within 24 months and the benefit of matching data across programs. Sexually transmitted infection screening may be warranted for male shigellosis case-patients.